Islamic Boarding Schools and Technology: Efforts to Overcome Social Changes in Santri Misuse of Gadgets - Rachmad Arif Ma’ruf; Darmanto Darmanto; Mohamad Haditia; Fatimatul Asroriah; Bima Fandi Asy'arie; Zuhairi Zuhairi (STAI Hubbulwathan Duri, 2024)
Islamic boarding schools have agreed that the prohibition on bringing electronic devices into the Islamic boarding school environment is not permitted. This prohibition aims to avoid having a negative impact on students in terms of using gadgets. This aims to reduce changes in social behavior that occur among students due to the switch to gadgets. The aims of this research are (1) to determine the form of social change in students with the support of gadgets. (2) knowing students' efforts in responding to social changes in gadgets. Then, this research is field research, the method used is a case study with a qualitative approach. The data collection techniques used are observation, interviews, and documentation. The findings in this research are: First, forms of social change in santri include decreased discipline, spiritual development, disruption of sleep patterns, frequent leaving of Islamic boarding school without permission from administrators, reduced social interaction, reduced enthusiasm for learning, and decreased morale to learn. enthusiasm for work. Second, the efforts of teachers/kyai in responding to social change among students, including as educators, leaders, motivators and facilitators. This research can then be used as a reference for other Islamic boarding schools that are facing technological challenges. When technology is used as a medium for student learning, educators must ensure that the Islamic religious values and traditions that underlie education in Islamic boarding schools are not neglected.